KARAKTERISTIK ORGANOLEPTIK DAN KIMIA BAKSO IKAN MUJAIR (Oreochromis mossambicus) YANG DISUBSTITUSI DENGAN TEPUNG SAGU (Metroxylon sago) SEBAGAI BAHAN PENGISI - Damopolii. R; Assa. J. R; Kandou J (COCOS, 2017)
ABSTRACTThe purpose of this study was to determine the effect of substitution of sago flour to the organoleptic and chemical characteristics of tilapia fish meatballs and to determine the ratio of sago flour and tapioca flour accurate and preferred by consumers as a filler of tilapia fish meatballs material. This study uses a completely randomized design (CRD) with 5 treatments, 50% of sago flour : 50% of tapioca flour, 60% of sago flour : 40% of tapioca flour, 70% of sago flour : 30% of tapioca flour, 80% of sago flour : 20 % tapioca flour, 90% of sago flour : 10% of tapioca flour. The results showed all the organoleptic treatment tilapia fish meatballs with a mixture of sago flour and tapioca flour for flavor has an average value of 3.84 (like), aroma 3.84 (like) and the texture of 3.72 (like), preferably panelists. In the protein test tilapia fish meatballs highest of treatment E 90% of sago flour and 10% of tapioca flour is 10.63%.Keywords : Tilapia fish meatballs, sago flour, tapioca flour